Pathogenesis and treatment of Sjogren’s syndrome: Review and update - Zhan, Qipeng; Zhang, Jianan; Lin, Yubin; Chen, Wenjing; Fan, Xinzou; Zhang, Dunfang (Frontiers in Immunology, 2023)
Primary Sjogren’s syndrome (pSS) is a chronic autoimmune disease accompanied by multiple lesions. The main manifestations include dryness of the mouth and eyes, along with systemic complications (e.g., pulmonary disease, kidney injury, and lymphoma). In this review, we highlight that IFNs, Th17 cell-related cytokines (IL-17 and IL-23), and B cell-related cytokines (TNF and BAFF) are crucial for the pathogenesis of pSS. We also summarize the advances in treatment strategies, including targeting of the Treg/Th17 axis, TNF-α/BAFF axis, and JAK pathway. Similar to that of SLE, RA, and MS, biotherapeutic strategies of pSS consists of neutralizing antibodies and inflammation-related receptor blockers targeting proinflammatory signaling pathways. However, clinical research of pSS therapy is comparatively rare. Moreover, the differences in the curative effects of immunotherapies among pSS and other autoimmune diseases are not fully understood. We emphasize that targeted drugs, low-side-effect drugs, and combination therapies should be the focus of future research.